A qualitative description of how Ghanaian radiographers identify suspected child physical abuse. Issue 4 (November 2021) - Antwi, W.K.; Reeves, P.; Christine, F.; Aziato, L.
Abstract: Introduction: Child physical abuse is intentionally inflicted injury of a child and presents a challenging diagnosis to clinicians mostly as a result of doubts about whether the findings were perpetrated by carers of these children. Suspected child physical abuse cannot be reported without its initial identification, substantiation and reporting. Imaging findings is one way of providing evidence of abuse in court. Methods: A qualitative design was used to gather data. Twenty (20) radiographers were recruited using purposive criterion sampling to share their experiences of mode of identification of suspected child physical abuse. Semi-structured interviews were conducted to gain deeper insight into their experiences. Results: Radiographers' suspicion or identification of child physical abuse was based on four (4) constructs: pre-radiographic observation; child's physical signs; caregiver secrecy and imaging findings. These observations provoked further investigations through questioning of the child (if of verbal age), parent or both. Their initial suspicion through assessment of cases was sometimes strengthened by the imaging findings. Conclusion: Radiographers suspected child physical abuse using several approaches some of which were found to be unacceptable although it led to other important information, such as additional imaging performed by the radiographers without doctor consultation. However, being able to identify child physical abuse is important in child protection activities. Implication for practice: Identification and reporting of suspected abuse to the appropriate child protection authorities are imperative for child protection. The possibility that some experienced radiographers may fail to deal with serious instances of child abuse exist. A radiographer's inability to identify such cases, could that the victim would miss the required protection from the professional.